Curricularização da extensão: Propostas de universidades federais paulistas - Lucimara Del Pozzo Basso; Adriana dos Santos Reis Lemos; Pedro Henrique Pimenta; Elisangela de Souza Bezerra; Maria Antonia Ramos de Azevedo; Fernando Stanzione Galizia (Universidade Federal da Fronteira Sul, 2023)
Curricularization of extension education: Proposals from the federal universities of São Paulo Abstract: This article analyzes the proposals for the curricularization of university extension education at the Federal University of ABC (UFABC) and the Federal University of São Paulo (UNIFESP). Although the State of São Paulo has a third federal university, we did not explore the Federal University of São Carlos (UFSCAR) because, to the date this work is written, no proposal for an extension education curriculum has been presented by the institution. The research is characterized by the qualitative modality, using the documental analysis method to explore the conceptions of extension, as well as the proposals of curricularization from the institutions. Because of that, the study was carried out within the Institutional Pedagogical Projects, Institutional Development Plans, and autonomous institutional documents were developed to standardize the curriculum. From our analysis, it was possible to observe similarities regarding the direction of extension as a curricular element not disconnected from the university context. However, both proposals are still timid in their pedagogical function toward the extension objectives, turning them into documents that only touch the technical aspects of the curricularization's implementation. Keywords: Higher Education; University Pedagogy; University Extension